Jewish Babylonia between Persia and Roman Palestine - Kalmin, Richard L. (Oxford University Press, 2006)
Roman persecutions of Jews -- Kings, priests, and sages -- Jewish sources of the Second Temple Period in rabbinic compilations of late antiquity -- Anxious rabbis and mocking non-rabbis -- Idolatry in late antique Babylonia -- Persian persecutions of the Jews -- Josephus in Sasanian Babylonia